Language Attitudes and Practices in Multilingual Setting: A Case Study of University Students in Bali - Putra, I Gde Agoes Caskara Surya; Tustiawati, Ida Ayu Mela (Bina Nusantara University, 2024)
The research aimed to investigate the language attitudes and practices of English Literature Study Program students in Bali towards Balinese, Indonesian, and English. Furthermore, the research also sought to determine whether the students’ attitudes affect their language practices daily. Applying a qualitative case study approach, the present research used a questionnaire and semi-structured interviews to collect data from the 100 participants. Results from the collected data reveal that the participants have similarly positive attitudes towards Balinese, Indonesian, and English. However, their language practices differ significantly: they practice Indonesian positively, while practices for Balinese and English are negative. It highlights a complementary relationship between language attitude and practice for Indonesians but a contradictory relationship between Balinese and English. Notably, the research identifies a generational shift in the practice of Balinese and a potential replacement by English among the cohort in particular and the young generation in Bali generally. These findings underscore the urgency of promoting and preserving the practice of Balinese. The research contributes novel insights into the impact of English on the linguistic dynamics of youth in Bali, especially those who enroll in English Language Programs at universities in Denpasar.